PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY: UKURAN DAN PERTUMBUHAN PERUSAHAAN, SERTA RISIKO KEUANGAN - Nisha Octarina; Majidah Majidah; Muhamad Muslih (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2018)
This research aims to determine the affect of size, growth, and leverage to the corporate social responsibility disclosure of the plantation companies in Indonesia, Malaysia, or both countries during 2013-2015. Purposive sampling method was used, obtained from 15 companies in Indonesia and 38 in Malaysia. Descriptive and multiple linear regression analysis were used in this research. The result shows that simultaneously, the size, the growth, and the leverage significantly affects CSR disclosure of the plantation companies in Indonesia, Malaysia, or both countries. In Indonesia, the size partially affect, growth does not affect, while leverage negatively affect of CSR disclosure. In Malaysia, the size and growth does not affect, while leverage has positive effect on the CSR disclosure. In both countries, the size has positive affect, while growth and leverage does not affect the CSR disclosure.